Is Balance Control Affected by Sleep Deprivation? A Systematic Review of the Impact of Sleep on the Control of Balance - Umemura, Guilherme Silva; Furtado, Fabianne; Santos, Fabia Camile dos; Gonçalves, Bruno da Silva Brandão; Forner-Cordero, Arturo (Frontiers in Neuroscience, 2022)
Background Sleep is a complex physiological function that should be addressed from different perspectives and consider the circadian rhythm. Sleep deprivation, either acute or chronic, negatively affects several functions, including motor control. Balance control is essential in several daily life activities and balance problems are related to falls. Research Question This review focuses on how sleep conditions impact balance control. Methods Systematic literature review according to PRISMA guidelines. Results The literature provided strong evidence that acute sleep deprivation impairs postural control. Chronic sleep deprivation as well as low sleep quality had similar effects, although there is a lower number of works addressing this issue. Furthermore, time awake worsens postural controls and it can be used to detect sleepiness and fatigue. The sleep deprivation showed a stronger negative effect on postural control when removing the visual information (eyes closed) than when reducing proprioceptive feedback (soft surface). There is scarce literature about the effects of chronotype, circadian patterns and chronic sleep deprivation, a frequent problem, on balance control; however they consistently indicate that there is an relationship between them. Most of the studies only consider one-night (acute) sleep deprivation without monitoring prior sleep conditions and the circadian rhythm phase of the participants. However, a few studies indicated that these factors must be considered. Significance These results suggest that the sleep conditions of a subject should be considered for several days prior to balance control tests. Therefore, we propose a revision of current postural measurement protocols to include sleep assessment, such as sleep quality questionnaires or actimetry, and to consider the circadian rhythm of the participants to plan the hour of the tests.